Ionosphere disturbance during cosmodrome “Vostochniy” launches - Dumbrava Zinaida F.; Sivokon Vladimir P.; Teslyuk Yuriy A.; Khomutov Sergey Y. (E3S Web of Conferences, 2018)
It is known that during spacecraft launches ionospheric plasma properties are modified in the result of impact of shock-acoustic waves generated during carrier rocket supersonic motion. As a rule, investigation of ionospheric plasma variations is carried out by the signals of Global Navigation Satellite Systems GPS/GLONASS that implies ground station network. There is no such a system near the “Vostochniy” cosmodrome that makes it necessary to search for an alternative solution. One of them may be the application of ionosphere vertical and oblique sounding stations. Based on the analysis of such station data, the possibility of evaluation of ionosphere modification during “Vostochniy” cosmodrome launches is shown.